The weight loss blogosphere: an online survey of weight loss bloggers - Evans, Martinus (Transl Behav Med, 2015)
Blogging is a form of online journaling that has been increasingly used to document an attempt in weight loss. Despite the prevalence of weight loss bloggers, few studies have examined this population. We examined characteristics of weight loss bloggers and their blogs, including blogging habits, reasons for blogging, like and dislikes of blogging, and associations between blogging activity and weight loss. Participants (N = 194, 92.3 % female, mean age = 35) were recruited from Twitter and Facebook to complete an online survey. Participants reported an average weight loss of 42.3 pounds since starting to blog about their weight loss attempt. Blogging duration significantly predicted greater weight loss during blogging (β = −3.65, t(185) = −2.97, p = .003). Findings suggest that bloggers are generally successful with their weight loss attempt. Future research should explore what determines weight loss success/failure in bloggers and whether individuals desiring to lose weight would benefit from blogging. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13142-015-0350-z) contains supplementary material, which is available to authorized users.